CO2 quality control through scrubbing in oxy-fuel combustion: An evaluation of operational pH impacts, and prediction of SO2 absorption rate at steady state. (January 2015) - Liu, Dunyu; Wall, Terry; Stanger, Rohan
Highlights: Steady state experiments were conducted in a continuous well stirred reactor. The relationship between the effectiveness of Na + and pH was determined. The absorption rate of SO2 primarily increases with pH. Operational pH (pH 5–6) is recommended in region 2. The instantaneous model overestimates the absorption rates of SO2 at pH below 6. Abstract: Oxy-fuel combustion is a promising CCS technology which is being demonstrated prior to commercialisation. While the flue gas in oxy-fuel combustion is concentrated in CO2, it contains impurities such as SO2 . The elimination of SO2 can provide a clean CO2 stream ready for storage. This paper is to understand the absorption of SO2 in scrubbing relevant to those used in oxy-fuel technology. Steady state experiments were conducted in a continuous well stirred reactor to understand the absorption rate of SO2 /CO2 into a total concentration of 0.28 M of mixtures of NaHSO3 and NaHCO3 simulating liquids formed by scrubbers using NaOH as the reagent at solution pH values from 4 to 7 with the exiting gas concentrations of SO2 from 19 ppm to 1500 ppm and a constant CO2 concentration of 70%. Online measurement included gas phase SO2 and liquid pH, and offline measurement included CO2 (aq), HCO3 −, S (IV), SO3 2− and S (VI) after each experiment. Three aspects investigated were the impacts of pH on the solution chemistry, the significance of solution pH and the concentration of gas phase SO2 on the absorption rate of SO2 . The total sulphur concentration in liquid was found to be related to the effectiveness of Na + . The effective ratio of Na + can be defined as the total sulphur to Na + ratio and this effectiveness ratio of Na + is pH dependent. At pH < 5, Na + is 99% effective. It reduces dramatically from 99% at a pH 5 to less than 15% at pH above 7. With regard to carbon based species also absorbed, super saturation of CO2 (aq) was observed at pH > 5.5. The concentration of HCO3 − increases dramatically above pH 6 and below this pH, the concentration of HCO3 − is negligible. The absorption rate of SO2 was found to increase with pH with some increase with the concentration of SO2 . The operational pH window for scrubbing may be defined by an upper limit pH where the absorption rate of SO2 starts to decreases from the maximum absorption rate of SO2 and the lower limit pH where the absorption rate of SO2 reduces to half of the maximum absorption rate of SO2 . Both the upper limit and the lower limit decrease initially and stay stable with the concentration of SO2 . This decrease is caused by the reversible reaction of the hydrolysis of SO2 and confirmed by equilibrium experiments of SO2 and sodium solutions. Operation within region 2 (pH 5–6) is recommended, depending on the scrubber design. The operation exit pH of the produced liquid can be varied within the region. The absorption rates of SO2 obtained in the steady state experiments were predicted by a model based on the instantaneous reaction assumption. This model generally overestimates the absorption rates of SO2 at pH values below 6 indicating a kinetic limitation of SO2 and water reaction at low pH values. The analysis on the controlling regions indicates that the gas side mass transfer resistance decreases with the concentration of SO2 . Liquid side resistance becomes more important at a lower pH and a higher concentration of SO2 .